PBLRQA model to the development of metacognitive awareness in pre-service teachers - Leasa, Marleny; Rengkuan, Mariana; Batlolona, John Rafafy (Intelektual Pustaka Media Utama, 2024)
Metacognition is one of the key learning skills in the 21st century, with a strong potential to help students succeed in science learning. Until now, this metacognitive awareness is less empowered by lecturers in learning. This study aimed to analyze the problem-based learning (PBL) reading-questioning-answering (PBLRQA) model's effect on metacognitive awareness in pre-service teachers. This research is a quasi-experiment with a pretest-posttest nonequivalent control group design. Determination of the research sample class was carried out by random sampling. Each learning model was represented by PBLRQA and PBL class. The number of classes used was 2, totaling 57 students. The instrument used was the metacognitive awareness inventory (MAI). This inventory comprised 52 statement items divided into planning, monitoring, evaluating, and revising skills. An important finding in this research is that students' metacognitive awareness in learning with PBL and PBLRQA is not significantly different. Thus, the PBLRQA and PBL models can still be used in students' science learning to encourage metacognitive awareness, so that academic success can be achieved.